Prospectus Liability of Investment Firms on the Basis of their Compulsory Intermediation on Capital Market Towards Securtiries Bayers in the Light of Special Law and General Civil Liability in Poland and Germany - Mijal, Piotr (Journal of Finance and Financial Law, 2016)
Article presents situations, which require compulsory intermediation of investment firm on Polish capital market with reference to public offer. Author analysis possibility of bearing responsibility for faulty prospectus on the basis of Polish Civil Code being inspire by solutions existing in German law order. The main of the paper is to broaden chances of non-professionals on capital market to cover their damages if they appear because of faulty prospectus, especially when issuer announces emergency public offer that should make possible avoiding insolvency.